HUBUNGAN DARI MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT GENERASI KREATIF MUDA INDONESIA - Desya, Calista Sarah (Universitas Kristen Indonesia, 2019)
This research about the relationship from motivation and work environmental to the perfomance of employee PT Generasi Kreatif Muda Indonesia. This research is a knowledge to know whether there is correlation of motivation and work environmental to the employee’s perfomance. The method of the research used is quantitaive method and used the set of a questionnaire. Population and sample of the research are 34 people. The questionnaire was given to the sample. After data was collected, then it was analyzed, and after that finding was drawn, the finding there is correlation of motivate and work environmental to employee’s perfomance. In order to maintain and improve employee’s perfomance, motivation and work environment PT Generasi Kreatif Muda Indonesia are important element that needs to more concern. Keywords: Motivation, Work Environment, and Employee Perfomance